AB0666 Renal resistive index in lupus nephritis: Correlation with renal function and association with histological features. (23rd January 2014) - Ceccarelli, F.; Perricone, C.; Gigante, A.; Spinelli, F.R.; Truglia, S.; Miranda, F.; Conti, V.; Massaro, L.; Cianci, R.; Valesini, G.; Conti, F.
Abstract : Background: Resistive Index (RI) is a simple parameter used to calculate the resistance of the walls of an artery calculated in color-Doppler ultrasonography (US) as [(peak-systolic velocity - end-diastolic velocity)/peak-systolic velocity]. Recent studies have shown that the RI of the renal artery is associated with tubule-interstitial lesions and vascular lesions. Few data are available concerning the role of RI in SLE nephritis. Objectives: Aim of this study was to analyze the association between intrarenal arterial RI, evaluated with color-Doppler US, functional renal indices and histological features of SLE patients. Methods: Patients affected by SLE, according with 1987 ACR criteria, candidate to kidney biopsy were enrolled. The functional renal assessment was performed (serum creatinine and blood urea nitrogen (BUN) levels, urinary protein excretion in 24 hours, estimated glomerular filtration rate [eGFR]). Kidney biopsy was performed and the class of nephritis was assessed according to the WHO classification. Color-Doppler US evaluation of intrarenal arterial RI was performed on the same day of kidney biopsy. RI greater than 0.7 was considered above normal. Results: Fourty-two patients were enrolled (M:F 1:41, mean age 34.2±10.6 years; mean disease duration 122.4±85.8 months; mean creatinine levels 1.4±1.2 mg/dl; BUN 41.4±39.9 mg/dl; urinary protein extraction 2.1±2 gr/24h; eGFR 78.4±42.3 mL/min). According to WHO classification, 7 patients (16.6%) had class II nephritis, 13 (30.9%) class III, 18 (42.8%) class IV, and 4 (9.5%) class V. RI was 0.64±0.08, five (11.9%) patients had RI>0.7. The RI showed a significant correlation with mean age (P=0.01, r=0.37), creatinine levels (P=0.01; r=0.37), BUN levels (P=0.04; r=0.32) and eGFR (P=0.007; r=0.42). Subgrouping patients according to eGFR, patients with eGFR<60mL/min showed mean RI significantly higher than patients with eGFR>60mL/min (0.66±0.09 vs 0.6±0.05, P=0.02). Dichotomizing the patients between those with RI≤0.7 and those with RI>0.7, we observed a higher prevalence of patients with RI>0.7 in class IV nephritis patients (4/5, 80%), compared with patients with class II, III and V nephritis class (P<0.0001, P=0.009 and P<0.0001, respectively). Indeed, patients with class IV nephritis showed a trend to higher mean RI levels (0.65±0.1); than that from other classes (class II: 0.62±0.005; class III 0.62±0.07; class V 0.61±0.02, P=NS). When considering the specific histopathologic features of the biopsies, RI>0.7 was more frequent in the presence of global sclerosis (15.4% vs 6.2%, P=NS), interstitial fibrosis (14.3% vs 7.1%, P=NS), tubular atrophy (13.3% vs 8.3%, P=NS). Conclusions: We found a significant correlation between renal arterial RI and renal functional. Moreover, a significant association was found with the histopathologic WHO classes. Larger longitudinal study are needed to confirm these results. Disclosure of Interest: None Declared